Die verhouding tussen gemeentelike en institusionele diakonaat – ’n Geïntegreerde model - Rudolph B. van Aarde (Verbum et Ecclesia, 2023)
The relationship between congregational and institutional diaconate – an integrated model. In this study the relationship between the congregational diaconate or ministry of compassion and the professional institutionalised social services of church-based welfare organisations is researched. Although the study focusses on the developments within the Dutch Reformed Church, the distance or separation between these services seems to be a general tendency also in other church denominations in the South African and global context. After the promulgation of the Act on Non-Profit Organisations (Act 71 of 1997), the ministry of compassion in congregations and the professional social services of the church’s welfare organisations drifted apart to such an extent that the two ministries developed each in its own silo. This silo-development resulted in separate languages for service delivery with a great deal of terminology confusion. – an integrated model